Mentoring Uncertified Teachers in Guyana (Global Journal of Human-Social Science, 2023)
In 2022 Guyana s Ministry of Education began a teacher licensing system highlighting the need for continuous development Teacher quality is a challenge in many developing countries The research question that guided this study was how does a customized professional development intensive mentoring program influence the preparation of uncertified teachers in Guyana as it relates to their lack of pedagogical content knowledge and classroom management skills Data were collected and analyzed using the Delphi Technique a group decision-making method to reach a consensus that identified what a customized professional development solution for uncertified teachers in two high schools in Guyana entailed specifically an intensive mentoring intervention Results from this study showed that a customized professional development intensive mentoring training program could be beneficial for uncertified teachers in Guyana The findings implied the presence of collaboration support and collegially sharing ideas and strategies that address evidence-based teaching practices